Regression of environmental noise in LIGO data. (28th July 2015) - Tiwari, V; Drago, M; Frolov, V; Klimenko, S; Mitselmakher, G; Necula, V; Prodi, G; Re, V; Salemi, F; Vedovato, G; Yakushin, I
Abstract: We address the problem of noise regression in the output of gravitational-wave (GW) interferometers, using data from the physical environmental monitors (PEM). The objective of the regression analysis is to predict environmental noise in the GW channel from the PEM measurements. One of the most promising regression methods is based on the construction of Wiener–Kolmogorov (WK) filters. Using this method, the seismic noise cancellation from the LIGO GW channel has already been performed. In the presented approach the WK method has been extended, incorporating banks of Wiener filters in the time–frequency domain, multi-channel analysis and regulation schemes, which greatly enhance the versatility of the regression analysis. Also we present the first results on regression of the bi-coherent noise in the LIGO data.